Genetic Background of Taste Perception, Taste Preferences, and Its Nutritional Implications: A Systematic Review - Diószegi, Judit; Llanaj, Erand; Ádány, Róza (Frontiers in Genetics, 2019)
Background: The rise in nutrition-related morbidity and mortality requires public health intervention programmes targeting nutritional behavior. In addition to socio-economical, socio-cultural, psychological determinants taste is one of the main factors that influence food choices. Differences in taste perception and sensitivity may be explained by genetic variations, therefore the knowledge of the extent to which genetic factors influence the development of individual taste preferences and eating patterns is important for public policy actions addressing nutritional behaviors. Our aim was to review genetic polymorphisms accounting for variabilty in taste and food preferences to contribute to an improved understanding of development of taste and food preferences. Methods: The electronic databases PubMed, Scopus and Web of Science were searched using MeSH in PubMed and free text terms for articles published between January 1, 2000 and April 13, 2018. The search strategy was conducted following the PRISMA statement. The quality of the included studies was assessed by the validated Q-Genie tool. Results: Following the PRISMA flowchart, finally 99 articles were included in the review. Among the reviewed studies, 39 were rated to have good quality, 47 were rated to have moderate quality and 13 were rated to have low quality. The majority of the studies assessed the association of genetic variants with the bitter taste modality, followed by articles analyzing the impact of polymorphisms on sweet and fat preferences. The number of studies investigating the association between umami, salty and sour taste qualities and genetic polymorphisms was limited. Conclusions: Our findings suggest that a significant association exists between TAS2R38 variants (rs713598, rs1726866, rs10246939) and bitter and sweet taste preference. Other confirmed results are related to rs1761667 (CD36) and fat taste responsiveness. Otherwise further research is essential to confirm results of studies related to genetic variants and individual sensitivity of the gustatory pathway. This knowledge may enhance our understanding of the development of individual taste and related food preferences and food choices that will aid the development of tailored public health strategy to reduce nutrition-related disease and morbidity.